Analisis Strategi Bisnis Berbasis SWOT pada PT Sauna Rahaf Utama - Kuncoro Wibowo; Samuel Horas Sarjana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to formulate an appropriate business development strategy for PT Sauna Rahaf Utama to navigate the competitive landscape of the engineering services industry. Utilizing the SWOT analysis framework (Strengths, Weaknesses, Opportunities, Threats), the research evaluates the firm’s competitive standing across internal and external dimensions. A qualitative descriptive methodology was employed, utilizing secondary observations and corporate document analysis. The findings, derived from IFAS and EFAS matrix calculations, yielded a total score of 2.95, positioning the company in Quadrant I (Aggressive Strategy). The primary strengths identified include operational experience since 2016 and a robust portfolio of state-owned enterprise (SOE) clients. Conversely, critical weaknesses lie in limited digital brand presence and a lack of international certifications. Consequently, the study recommends a growth-oriented strategy focusing on strengthening digital identity, obtaining ISO certifications to bolster competitiveness, and innovating technology-based services to capitalize on emerging opportunities within the mining and infrastructure sectors.